Dili is rare amongst patients without liver metastases receiving cancer treatment in Iceland: a population-based cohort study. - Björnsson, H K; Sverrisdottir, A; Björnsson, E S (Scandinavian Journal of Gastroenterology, 2022)
To access publisher's full text version of this article click on the hyperlink below Background: There is limited information on the frequency of idiosyncratic drug-liver injury (DILI) among cancer patients. The aim of the study was to evaluate the frequency of DILI due to cancer treatment in a population-based setting. Material and methods: All patients diagnosed with genitourinary cancer, breast cancer or metastatic malignant melanoma in 2007-2018 were matched with a database containing laboratory results for all major hospitals in Iceland. Medical chart review was performed for cases with ALT/AST ≥5× upper limit of normal (ULN), ALP ≥2× ULN or bilirubin ≥2× ULN. Patients with liver-, and/or bone metastases and isolated elevations of ALP and patients with other etiologies of liver enzyme elevations were excluded. Cases with a RUCAM score of probable or highly probable were included. Results: Among 4956 patients, 840 patients had liver enzyme elevations. Overall, nine (0.2%) cases of DILI were identified, seven women (78%), median age 59 years (IQR 52-66). Four patients had kidney cancer, four breast cancer and one metastatic prostate cancer. In eight cases, a single agent was implicated: Pazopanib (n = 3), axitinib, docetaxel, gemcitabine, letrozole and paclitaxel. In all cases, the treatment was interrupted or discontinued due to the liver injury. No patient developed jaundice or liver failure and no death was linked to DILI. Time to normalization of liver enzymes was 17 days (IQR 25-120). Conclusion: DILI was found to be rare and no cases of severe liver injury occurred. However, approximately 90% of patients switched to another treatment which might have affected prognosis. Keywords: DILI; RUCAM; hepatotoxicity; liver enzymes; malignancy. Landspitali University Hospital